Collaboration between Government and Private Sector in Improving Village Economy in Jeneponto Regency - Rahman, Abdul (Pusat Studi Pembangunan dan Pemberdayaan, 2023)
Public-private partnerships (PPPs) have emerged as a strategic approach to addressing economic challenges in rural areas, particularly in regions where traditional governmental efforts have been insufficient. This study examines the impact of PPPs on the economic development of villages in Jeneponto Regency, South Sulawesi, Indonesia. Through a combination of survey data from local stakeholders and quantitative analysis of key economic indicators, the study explores the correlation between PPP intensity measured by investment levels and outcomes such as income growth, employment rates, and access to essential services like education and healthcare. The results indicate strong positive correlations between PPP intensity and these economic outcomes, suggesting that increased investment through PPPs is directly linked to significant improvements in the socio-economic conditions of the villages. Stakeholder perceptions also align with these findings, with the majority expressing satisfaction with the effectiveness of PPPs in driving local development. Despite the study’s limitations, including a relatively small sample size, the evidence supports the conclusion that PPPs are a viable and effective strategy for fostering sustainable economic growth in rural regions. These findings have important implications for policymakers and private sector stakeholders, emphasizing the need for continued and expanded use of PPPs to address the persistent challenges of rural development. Future research should focus on larger datasets and longitudinal studies to further validate these findings.